A Systematic Review of the Current Role of Minimally Invasive Spine Surgery in the Management of Metastatic Spine Disease. (2nd June 2011) - Molina, Camilo A.; Gokaslan, Ziya L.; Sciubba, Daniel M.
Abstract : Although increasingly aggressive decompression and resection methods have resulted in improved outcomes for patients with metastatic spine disease, these aggressive surgeries are not feasible for patients with numerous comorbid conditions. Such patients stand to benefit from management via minimally invasive spine surgery (MIS), given its association with decreased perioperative morbidity. We performed a systematic review of literature with the goal of evaluating the clinical efficacy and safety of MIS in the setting of metastatic spine disease. Results suggest that MIS is an efficacious means of achieving neurological improvement and alleviating pain. In addition, data suggests that MIS offers decreased blood loss, operative time, and complication rates in comparison to standard open spine surgery. However, due to the paucity of studies and low class of available evidence, the ability to draw comprehensive conclusions is limited. Future investigations should be conducted comparing standard surgery versus MIS in a prospective fashion.